ANALYSIS OF FACTORS INFLUENCING THE CONSUMPTIVE BEHAVIOR OF STUDENTS USING SHOPEE IAIN SYEKH NURJATI CIREBON - Ebah Hijriani; Refaldo Fanther; Abdul Muiz Abdul Wadud Kasyful Anwar (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2024)
Consumptive behavior is the act of someone buying an item without reasonable consideration where a person in buying an item is not based on the need factor. This study aims to determine and analyze whether Financial Literacy, Self-Control and Peer Environment affect the Consumptive Behavior of Students using Shopee IAIN Syekh Nurjati Cirebon. The data used are primary data in the form of questionnaires and secondary data in the form of journals, articles and other sources. The population in this study was IAIN Syekah Nurjati Cirebon students with a sample of 100 respondents and used multiple linear regression model analysis assisted by SPSS 23. The results showed that partially the variables of Financial Literacy had a negative and significant effect on consumptive behavior, Self-Control and Peer Environment had a positive and significant effect on Consumptive Behavior. Then simultaneously, the variables Financial Literacy (X1), Self-Control (X2), and Peer Environment (X3) were simultaneous influences on Consumptive Behavior (Y). As seen from the table of coefficients of determination (R2), it can be seen that the value of R Square shows the number 0.453. This explains that the variables Financial Literacy, Self-Control, and Peer Environment on Consumptive Behavior can affect as much as 45%, while the remaining 55% are influenced by other variables outside the study.